2023
DOI: 10.3389/fpls.2023.1242463
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi improve selenium uptake by modulating root transcriptome of rice (Oryza sativa L.)

Yan Qin,
Qiuliang Cai,
Yiting Ling
et al.

Abstract: Although selenium (Se) is an essential trace element in humans, the intake of Se from food is still generally inadequate throughout the world. Inoculation with arbuscular mycorrhizal fungi (AMF) improves the uptake of Se in rice (Oryza sativa L.). However, the mechanism by which AMF improves the uptake of Se in rice at the transcriptome level is unknown. Only a few studies have evaluated the effects of uptake of other elements in rice under the combined effects of Se and AMF. In this study, Se combined with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
1
0
0
Order By: Relevance
“…A previous research have indicated that inoculation with AMF can transfer beneficial elements to the host root system through symbiotic hyphae and improve the utilization of beneficial elements [40]. Inoculation with AMF can improve Se uptake by regulating the root transcriptome [41]. Furthermore, our study discovered that in the Se + AMF treatment, the shoot has the highest total Se concentration and the lowest available Cd concentration (Figs.…”
Section: Impact Of Se and Amf On CD And Se Concentrationssupporting
confidence: 58%
“…A previous research have indicated that inoculation with AMF can transfer beneficial elements to the host root system through symbiotic hyphae and improve the utilization of beneficial elements [40]. Inoculation with AMF can improve Se uptake by regulating the root transcriptome [41]. Furthermore, our study discovered that in the Se + AMF treatment, the shoot has the highest total Se concentration and the lowest available Cd concentration (Figs.…”
Section: Impact Of Se and Amf On CD And Se Concentrationssupporting
confidence: 58%